Children's vegetarian culture in the Victorian era - Kubisz, Marzena, author. Link
1 online resource.
Keywords: "This book fills a unique gap in the research on the cultural history of vegetarianism and veganism, children's literature and Victorian periodicals, and it is the first publication to systematically describe the phenomenon of Victorian children's vegetarianism and its representations in literature and culture. Situated in the broad socio-literary context spanning the late 19th century and early 20th century, the book lays the groundwork for contemporary children's vegan literature and argues that present ethical and environmental concerns can be traced back to the Victorian period. Following the current turn in contemporary research on children, their experience, and their voices, the author examines children's vegetarian culture through the prism of the periodicals aimed directly at them. It analyses how vegetarian principles were communicated to children and listens to the voices of children who were vegetarians, and who tested their newly formed identity in the pages of three magazines published between 1893 and 1914: The Daisy Basket, The Children's Garden and The Children's Realm. This book will appeal to the growing body of researchers interested in social, cultural and literary aspects of vegetarianism and veganism, human-animal relations, childhood studies, children's literature, periodical studies and Victorian studies"--